The Impact Of Occupational Safety Training On Employee Performance With Safety Culture As A Mediation Variable - Adinda Irma Syahputri; Zulfina Adriani; Tona Aurora Lubis (International Journal of Business and Quality Research, 2025)
This study examines the impact of Safety training on employee performance, with safety culture as a mediating variable at Pertamina Hulu Energi (PHE) Jambi Merang. The objectives of the research are to determine: (1) the direct effect of Safety training on employee performance, (2) the impact of safety culture on employee performance, and (3) the mediating effect of safety culture on the relationship between Safety training and employee performance. The research object consists of employees of PHE Jambi Merang, a company in the oil and gas sector with a high risk of workplace accidents. The population includes 70 employees, all of whom were selected as research participants using a total sampling technique. The analysis tool used in this study is Structural Equation Modeling (SEM), processed through SmartPLS software, to assess the relationship between Safety training, safety culture, and employee performance. The results are expected to provide valuable insights into improving the effectiveness of safety training programs and enhancing employee performance through strengthening the safety culture.